Pengembangan Pentapod Armor Beton Jenis Baru untuk Pelindung Bangunan Pantai - Natakusumah, Dantje Kardana; Achiari, Hendra; Nugroho, Eka; Hidayatulloh, Syarif; Angelo, Jonathan; Adinata, Fitra (Jurnal Teknik Sumber Daya Air, 2023)
This paper discusses PentaPod concrete armor, a new type of coastal structure protection made from concrete designed to shield against wave and tidal damage. PentaPod concrete armor can be arranged randomly or in an organized fashion without requiring ties. However, it can also be installed systematically, in one or multiple layers, interconnected with ties. The overall stability of structures with PentaPod armor far exceeds that of conventional concrete armor installations. The research method involves determining the Stability Coefficient (Kd) for two variants of PentaPod concrete armor, namely PentaCone and PentaOcta, tested in a Wave Tank. This study aimed to find the stability coefficient for both variants of PentaPod concrete armor when installed randomly and systematically without tie bonds. The novelty of the research includes that the concrete armor: 1) can be installed randomly and systematically, 2) systematic installation without ties reduces the number of armor units and associated costs, 4) systematic tie-bonded installation improves stability and can reduce the size of armor units, thus lowering costs, 5) the use of ties facilitates the installation of armor on the surface and underwater. In this paper, the Flow 3D software is used as a Numerical Wave Flume. Although there are no results from the Numerical Wave Flume that can be compared with the results from the Physical Wave Flume, this is an initial step toward obtaining complementary results between the Physical and Numerical Wave Flume methods.